The Impact of Pandemic COVID-19 To Cultural Heritage Tourism Prambanan Temple Compounds - Larasati Nuria Dewi (Journal of Mandalika Review, 2022)
COVID-19 outbreak began at the end of 2019, affecting various sectors around the world, including Indonesia's tourism sector, which saw major effects of COVID-19. Prambanan temple compounds, located in Sleman Regency, Yogyakarta Special Region, has also been affected by Covid-19. This research aims to identify the general profile of Prambanan temple compounds, the impact of Covid-19 on the Prambanan temple compounds and identify the next action by stakeholders to develop Prambanan temple compounds during and after the Covid-19 pandemic. The type of research used is qualitative to describe the situation and conditions that occur in the field as they are. This study took place in the Prambanan Temple Compounds, which is located in Prambanan District, Sleman Regency, Special Region of Yogyakarta. Data collection techniques in this study were in-depth interviews, observation and document review. Prambanan, the largest Hindu temple compound in Indonesia that consist of Prambanan Temple (also called Loro Jonggrang), Sewu Temple, Bubrah Temple and Lumbung Temple, The Prambanan site, has been designated as one of the strategic national areas and managed by Taman Wisata Candi, Ltd (TWC). Prambanan Temple Compounds has been badly affected by COVID-19. During the pandemic, there was a drastic decrease in the number of tourists, both domestic and foreign tourists. PT TWC adapts to the conditions by taking various actions and strategies in order to create a safe and attractive environment for the tourists.